2022
DOI: 10.21203/rs.3.rs-1323292/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High Temperature and Water Deficit Cause Epigenetic Changes in Somatic Plants of Pinus Radiata D. Don

Abstract: Current climate changes imply an imminent risk for forest species. In this context, somatic embryogenesis is a valuable tool to study the response of plants to different abiotic stresses. Based on this, we applied a high-temperature regime (50 ºC, 5 min) during the maturation of Pinus radiata D. Don embryogenic masses in order to evaluate the development of an epigenetic memory months later. Therefore, somatic plants (SP) resulting from somatic embryos (ses) maturated at control temperature and cultivated in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
0
0
Order By: Relevance
“…Relative water content is a critical indicator reflecting the water status of plants [23]. The results of this study showed that the relative water content of C. oleifera petals decreased significantly under drought stress, indicating that the petal is significantly affected by drought stress; this finding is consistent with previous studies [24].…”
Section: Discussionsupporting
confidence: 92%
“…Relative water content is a critical indicator reflecting the water status of plants [23]. The results of this study showed that the relative water content of C. oleifera petals decreased significantly under drought stress, indicating that the petal is significantly affected by drought stress; this finding is consistent with previous studies [24].…”
Section: Discussionsupporting
confidence: 92%